Which literacy for health promotion: health, food, nutrition or media?. (21st February 2019) - Truman, Emily; Bischoff, Madison; Elliott, Charlene
Abstract: Education and literacy are important aspects of health promotion. The potential for health literacy to promote healthier choices has been widely examined, with studies variously incorporating food literacy, nutrition literacy and/or media literacy as components of health literacy, rather than treating each as unique concepts for health promotion. This study examines similarities and differences across health literacy, food literacy, nutrition literacy and health-promoting media literacy to highlight how each literacy type theorizes the relationship between education and health. A meta-review of existing scoping and systematic reviews examining literacy conceptualizations was conducted to examine the four literacies. Representative concept definitions were extracted and key competencies (or skills) and desired consequences were identified and grouped into subcategories for analysis. This study located 378 articles, of which 17 scoping/systematic reviews were included (10 for health literacy, 3 for food, 1 for nutrition and 3 for media). Representative concept definitions of the four literacy types revealed three skill categories (information acquisition, information analysis, and the application of information) and three categories of desired consequences (knowledge, attitudes and behaviors), with each of the four literacy types emphasizing varied collections of skills and desired consequences. Despite perceived similarities in content, health, food, nutrition and media literacy conceptualize the relationship between education and health differently, emphasizing the distinct types of knowledge to promote health-related outcomes. A better understanding of the differences between these four literacies will lead to informed decision making for researchers, educators and health practitioners in intervention design and implementation.